Pengukuran Akuntansi Sumber Daya Manusia: Valuasi Pegawai Baru pada Entitas KPPN - Pierra Santos Halomoan Lumban Tobing (Direktorat Sistem Perbendaharaan, 2021)
Human resource is believed as one of the main subject in every development of an entity or institution. The challenges of very fast developments encourage various entities to take various approaches in developing human resources (HR) carefully, both from the initial stage of the entity's establishment, to the stage where the institution develops and then becomes an established entity or vice versa becomes bankrupt. Seeing the importance of the development and role of HR, various previous accounting studies have revealed that there is an effort to recognize and measure HR as the asset with the most important value in an organization. However, because the definition of HR as an asset is not met, the accounting standards for HR have never been set. Therefore, this paper will only attempt to describe the potential measurement of the monetary value of HR as an asset based on initial fundamental values ​​and factors without being influenced by the definition of assets in accounting standards, and how this measurement can be a tool for photographing the performance of a government entity unit without compromising value. individual monetary. In this study, it is concluded that the measurement of HR in monetary unit value can be carried out in the government sector using the Lev and Schwartz Model reformula approach and then discounted again with the present value annuity with growth.